Psychological Age Equity Approach to Increasing Dental Care Acceptance in Early Childhood - Sabda Alam; Mustriana (UNIVERSITAS PGRI MADIUN, 2024)
Anxiety and fear during dental procedures are common issues among young children, often hindering their acceptance of dental care and negatively impacting long-term oral health. Traditional approaches to dental care frequently fail to address children's psychological needs, resulting in negative experiences and avoidance of dental visits. This study investigates the effectiveness of the psychological age-equality approach in increasing children's acceptance of dental care by reducing anxiety and improving cooperation during dental procedures. A qualitative research design was employed, involving in-depth interviews with parents and dental professionals, along with direct observation of children aged 3–6 years undergoing dental procedures. These procedures incorporated age-appropriate psychological techniques. Thematic analysis was used to identify patterns and evaluate the impact of the approach on children's behavior and emotional responses.The findings revealed that the psychological age-equality approach significantly reduced children's dental anxiety and enhanced their cooperation during procedures. This approach effectively meets children's emotional and cognitive needs, improving their overall acceptance of dental care.